Understanding the Doppler effect by analysing spectrograms of the sound of a passing vehicle. (4th September 2017) - Lubyako, Dmitry; Martinez-Piedra, Gordon; Ushenin, Arthur; Denvir, Patrick; Dunlop, John; Hall, Alex; Le Roux, Gus; van Someren, Laurence; Weinberger, Harvey
Abstract: The purpose of this paper is to demonstrate how the Doppler effect can be analysed to deduce information about a moving source of sound waves. Specifically, we find the speed of a car and the distance of its closest approach to an observer using sound recordings from smartphones. A key focus of this paper is how this can be achieved in a classroom, both theoretically and experimentally, to deepen students' understanding of the Doppler effect. Included are our own experimental data (48 sound recordings) to allow others to reproduce the analysis, if they cannot repeat the whole experiment themselves. In addition to its educational purpose, this paper examines the percentage errors in our results. This enabled us to determine sources of error, allowing those conducting similar future investigations to optimize their accuracy.